2015
DOI: 10.1051/0004-6361/201425018
|View full text |Cite
|
Sign up to set email alerts
|

Combining high-dispersion spectroscopy with high contrast imaging: Probing rocky planets around our nearest neighbors

Abstract: Context. Ground-based high-dispersion (R ∼ 100 000) spectroscopy (HDS) is proving to be a powerful technique with which to characterize extrasolar planets. The planet signal is distilled from the bright starlight, combining ral and time-differential filtering techniques. In parallel, high-contrast imaging (HCI) is developing rapidly, aimed at spatially separating the planet from the star. While HDS is limited by the overwhelming noise from the host star, HCI is limited by residual quasi-static speckles. Both t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 280 publications
(271 citation statements)
references
References 47 publications
(61 reference statements)
4
266
0
1
Order By: Relevance
“…We suspect that the factor of 2 difference in detection significance may be attributed to the different approach in calculating the CCF S/N. Snellen et al (2015) investigated the detectability of a shortperiod super-Earth around Proxima Cen and concluded that the planet can be detected with a significance of 10 for a wavelength coverage from 0.6 to 0.9 μm with an HDC instrument on the E-ELT. Following the details in their paper, we found a CCF S/N of 4.0 for such a super-Earth.…”
Section: Comparison To Previous Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We suspect that the factor of 2 difference in detection significance may be attributed to the different approach in calculating the CCF S/N. Snellen et al (2015) investigated the detectability of a shortperiod super-Earth around Proxima Cen and concluded that the planet can be detected with a significance of 10 for a wavelength coverage from 0.6 to 0.9 μm with an HDC instrument on the E-ELT. Following the details in their paper, we found a CCF S/N of 4.0 for such a super-Earth.…”
Section: Comparison To Previous Resultsmentioning
confidence: 99%
“…At this low level of S/N per pixel, each absorption line is very noisy. Considering the proportionality of CCF S/N to the square root of the number of lines (Snellen et al 2015), we only expect a modest contribution from the line-resolved CCF, as shown in Figure 16, even if the spectral resolution is high enough to resolve individual absorption lines.…”
Section: Ccf At Low S/n (Per Pixel) Regimementioning
confidence: 97%
See 3 more Smart Citations